2000
DOI: 10.1207/s15327604jaws0302_2
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Reasons for Relinquishment of Dogs and Cats to 12 Shelters

Abstract: The Regional Shelter Relinquishment Study sponsored by the National Council on Pet Population Study and Policy (NCPPSP) is a national research project designed to explore the characteristics of relinquished dogs and cats, their owners, and the reasons for relinquishment. The NCPPSP Regional Shelter Study found that behavioral problems, including aggression toward people or nonhuman animals, were the most frequently given reasons for canine relinquishment and the second most frequently given reasons for feline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
231
3
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 412 publications
(263 citation statements)
references
References 10 publications
4
231
3
4
Order By: Relevance
“…Though most human -dog relationships are fulfilling, each year a large number of animals are abandoned by their owners or relinquished to animal shelters 4 . Aggression toward people and animals, running away, destructive behaviour, disobedience, house soiling and excessive barking are unwanted behaviours that make owners relinquish or abandon their dogs 5 . Although only 20 % of the dogs in the US shelters are assigned by their owners for euthanasia 6 , a further 40 % of dogs admitted are euthanised 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Though most human -dog relationships are fulfilling, each year a large number of animals are abandoned by their owners or relinquished to animal shelters 4 . Aggression toward people and animals, running away, destructive behaviour, disobedience, house soiling and excessive barking are unwanted behaviours that make owners relinquish or abandon their dogs 5 . Although only 20 % of the dogs in the US shelters are assigned by their owners for euthanasia 6 , a further 40 % of dogs admitted are euthanised 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Compared with non-shelter dogs, those sourced from shelters had significantly more whorls on the chest (58.24% vs. 41.76%; P < 0.001) and elbow (56.86% vs. 43.14%; P < 0.001). Salman et al (2000) reported that behavioral problems, including aggression, was the predominant cause of owners relinquishing dogs to shelters. Given that the cadavers had been sourced from a shelter and that dogs in shelters have usually either strayed or have been surrendered for behavioral reasons, the relationship between source and hair whorls was of interest because it may elucidate whether the presence of a whorl is an indicator of an undesirable behavioral trait.…”
Section: Whorl Presencementioning
confidence: 99%
“…A survey of caregivers (owners) with two or more cats revealed that if aggression occurred upon introduction of a new cat into a household with a resident cat, fighting was more likely to occur during the subsequent 12-month period compared with cats of owners who did not observe aggression upon initial introduction (Levine, Perry, Scarlett, & Houpt, 2005). Problems between new and resident cats, aggression toward other nonhuman animals, and being fearful cumulatively accounted for approximately 35% of the reasons cats were relinquished to animal shelters (Salman et al, 2000). Intercat aggression was the underlying cause for 42% of feline behavior cases presented to the University of Georgia Veterinary Behavior Service during a three-year period (Amat et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…House soiling is the leading singlebehavior cause of cats being relinquished to animal shelters (Salman et al, 2000). Inappropriate elimination use in cats housed indoors may be caused by medical or behavioral issues; this complex issue is known as Pandora syndrome (Buffington, Westropp, & Chew, 2014;Hart, Eckstein, Powell, & Dodman, 1993).…”
Section: Introductionmentioning
confidence: 99%